Review of psychological studies on correlates of youth religiosity in post-socialist Bosnia and Herzegovina - Srđan Dušanić (Sineza, 2023)
Research on religiosity in Bosnia and Herzegovina (B&H) and former Yugoslavia during the socialist period consistently shows that the majority of inhabitants (70–80%) identify as not religious. In the 1990s, many things changed in B&H, the most important definitely being the fall of the socialist system, expansion of ethnic awareness among all three dominant peoples (Bosniaks, Serbs, Croats), and ethnic war. These social circumstances were followed by changes in the relationship towards religion. Religion has become a very important and socially desirable ideology. In this survey, we review psychological surveys and investigate to what extent young people in the post-socialist context of B&H are religious, and we examine the relationship between religiosity and other social, psychological, and demographic variables. The results of close to 50 empirical surveys have been analysed. Papers were written in the period from 2000 to 2022. All papers included samples from B&H. The paper with the smallest sample had 163 respondents, while the biggest sample amounted to 7,000 respondents. The majority of papers had 300–550 respondents. All surveys encompassed young people between 15 and 25 years of age. The instruments used in most of the cases were the religiosity scales that rely on Allport’s concept of religious orientation, and they imply the existence of intrinsic and extrinsic dimensions (subscales) of religiosity. The results of most of the research show that around 70–90% of participants identify as religious. People in Bosnia and Herzegovina are keen on identifying as religious, but that is much less accompanied by adequate and concrete religious attitudes and behaviours. Socio-demographic variables can be important for expressing religiosity, but those correlations are not consistent. Religiosity almost regularly correlates with conformity, authoritarianism, and conservatism. There is a tendency that religiosity can be a determinant of personal well-being. Correlation is found with better family relations, altruism, lower anti-social behaviours, and, in some research, greater satisfaction with life and optimism. In contrast to that, religiosity can be connected with certain realistically or potentially problematic constructs such as social and ethnic distances, authoritarianism, dogmatism, and ethnocentrism. In the future, it is necessary to work on the development of religiosity, which is a factor of internal and social well-being, and not of intergroup disputes.